Exploring Carbon Emissions in the Construction Industry: A Review of Accounting Scales, Boundaries, Trends, and Gaps - Qinfeng Zhao; Zhirui Wu; Yi Yu; Tian Wang; Shan Huang (Buildings)
The construction industry, characterized by high energy consumption and carbon emissions, plays a pivotal role in climate change mitigation. This paper employs bibliometric analysis, based on 282 articles from the SCIE and SSCI in the Web of Science spanning 1992–2022, to explore research trends and themes in Carbon Emissions of Construction Industry (CECI). A manual review was conducted to identify challenges and possibilities concerning accounting scales, objects, boundaries, and methods in CECI research. Key findings include (1) temporal and thematic evolution, with a notable increase in research activity since 2015, primarily focusing on energy efficiency, sustainable development, green building technologies, and policy evaluation; (2) scale-specific gaps, as 80.7% of studies are conducted at macro (national/regional) or micro (building/material) levels, while city-scale analyses are significantly underrepresented, with only 13 articles identified; (3) object granularity deficiencies, with 74.8% of studies not distinguishing between building types, resulting in rural residential, educational, and office buildings being significantly underrepresented; (4) system boundary limitations, as few studies account for emissions from building demolition or the disposal and recycling of construction waste, indicating a substantial gap in life-cycle carbon assessments. Furthermore, the predominant reliance on the carbon emission factor method, along with embedded assumptions in accounting processes, presents challenges for improving carbon accounting accuracy. This review synthesizes insights into prevailing research scales, object classifications, system boundaries, and methodological practices, and highlights the urgent need for more granular, lifecycle-based, and methodologically diverse approaches. These findings provide a foundation for advancing CECI research toward more comprehensive, accurate, and context-sensitive carbon assessments in the construction sector.